2018
DOI: 10.1016/j.im.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

OSPM: A design methodology for open strategic planning

Abstract: This study employs a design science perspective to propose a methodology for open strategic planning (OSP). Habermas' discourse theory and Bryson's strategy change cycle are used as informing kernel theories. A methodology is proposed to satisfy the requirements retrieved from the kernel theories. The proposed methodology contains modules for a planning system, and a planning process. Design principles are explained through a blueprint of the system and process. The proposed methodology is applied and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 84 publications
0
16
0
1
Order By: Relevance
“…However, quality of life problems could be avoided—or could be less harmful—if more effective strategic planning and effort were put into place from the start (Castanho et al, 2021 ; Street, 1997 ). Various authors have suggested strategic planning that guides initiatives and activities as a tool to help managers achieve their organization’s objectives (Amrollahi & Rowlands, 2018 ; Brito et al, 2019 ; Klag & Langley, 2014 ; Poister & Streib, 2005 ). Also, Barney ( 1991 ), Mintzberg ( 1991 ), Del Pero ( 2013 ), Klag and Langley ( 2014 ), and Barney and Mackey ( 2018 ) recommend strategic plans that allocate resources efficiently and effectively to optimize entity performances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, quality of life problems could be avoided—or could be less harmful—if more effective strategic planning and effort were put into place from the start (Castanho et al, 2021 ; Street, 1997 ). Various authors have suggested strategic planning that guides initiatives and activities as a tool to help managers achieve their organization’s objectives (Amrollahi & Rowlands, 2018 ; Brito et al, 2019 ; Klag & Langley, 2014 ; Poister & Streib, 2005 ). Also, Barney ( 1991 ), Mintzberg ( 1991 ), Del Pero ( 2013 ), Klag and Langley ( 2014 ), and Barney and Mackey ( 2018 ) recommend strategic plans that allocate resources efficiently and effectively to optimize entity performances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Otwartość strategiczna, której urzeczywistnieniem jest otwarta strategia, określana jest jako nowy paradygmat zarządzania strategicznego 29 , będący zbiorem poglądów dotyczących zwiększenia w procesie formułowania strategii roli pomysłów na strategię spoza zespołu strategów (wyższych i niższych szczebli) oraz zapewnienia interesariuszom (konsultantom, klientom, dostawcom, a nawet konkurentom) dostępu do wkładu, procesu i wyników strategii, co dowodzi uczestnictwa osób spoza granic organizacyjnych 30 .…”
Section: Otwartość Strategiczna I Ramy Otwartej Strategiiunclassified
“…Recent studies (Amrollahi & Rowlands, 2016;Morton et al, 2016b;Tavakoli et al, 2015a) have highlighted the use of IT tools as a critical characteristic of open strategy. Using an online system is regarded as essential in attracting more stakeholders to participate, as well as providing a trustworthy and anonymous platform for them to submit their ideas.…”
Section: Implications For Practicementioning
confidence: 99%
“…For these reasons, the evolution of strategic planning research and practice has been of key interest to researchers, as new topics such as strategy as practice, decentralisation of strategy formulation, and IT-enabled strategic planning have emerged and altered the landscape of strategic planning (Chesbrough & Appleyard, 2007;Wolf & Floyd, 2013). OSP is one of these new topics extending the domain of strategic planning research by incorporating computerised information systems and recommending new IT tools for this purpose (Amrollahi & Rowlands, 2018). Accordingly, this paper claims that the notion of OSP can benefit from contributions from IS research.…”
Section: Introductionmentioning
confidence: 99%